'We actually get to go out and play': looking through children's views on Out of School Hours Care to children's experience of school. Issue 3 (3rd July 2021) - Moir, Persephone; Brunker, Nicole
ABSTRACT: Out of School Hours Care (OSHC) is recognised as an important service for working parents. Enabling parents to work beyond school hours, this sector has seen increased demand. Research and policy have provided insight into the nature of OSHC in relation to parent use and staff processes, with little consideration to the perspective at the core of this service – children. This small, exploratory project focused on children's perceptions of OSHC, adding to our understanding of children's perceptions of play. They identified key themes in relation to the importance of friends and social interaction; play and choice; and provision of technology for relaxation. Amidst the children's comments is a reflection on the increasing contrast between the value of play at OSHC and the busyness of school. This suggests there is a need for further research to better understand children's experience of OSHC, alongside their experience of and perspectives about school.